A STUDY ON POLYNOMIAL TERNARY SEMI RING - Rao, T. Srinivasa; Rao, D. Madhusudana; Kumar, B. Srinivasa (International Journal of Research -GRANTHAALAYAH, 2015)
In this paper we discussed about the polynomial ternary semiring and characterized them.